The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/j.1556-6676.2015.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Identity, Mental Health, HIV Risk Behaviors, and Internalized Homophobia Among Black Men Who Have Sex With Men

Abstract: The purpose of this study was to determine the relationships between sexual identity, depression, self-esteem, HIV risk behaviors, HIV status, and internalized homophobia in Black men who have sex with men. Results demonstrated a positive relationship between depression, HIV risk behaviors, and internalized homophobia; a negative relationship with self-esteem; and differences in internalized homophobia by HIV status (i.e., positive, negative, or unknown). Counseling recommendations are provided for working wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 35 publications
(40 reference statements)
6
36
0
Order By: Relevance
“…In a meta-analysis of the research examining IH and risky sex among MSM, Newcomb and Mustanski found only a small effect size and questioned the usefulness of further examining IH as a direct correlate of risky sexual behaviors (13). Even so, individual studies have found IH to be related to greater rates of condomless anal sex and higher numbers of anal sex partners (8, 10, 14). These inconsistencies in the literature on the relation between IH and condomless sex may reflect a need for more nuanced studies, such as examining indirect effects or moderating variables (15, 16).…”
Section: Minority Stress: Ih In Relation To Risky Behaviorsmentioning
confidence: 99%
“…In a meta-analysis of the research examining IH and risky sex among MSM, Newcomb and Mustanski found only a small effect size and questioned the usefulness of further examining IH as a direct correlate of risky sexual behaviors (13). Even so, individual studies have found IH to be related to greater rates of condomless anal sex and higher numbers of anal sex partners (8, 10, 14). These inconsistencies in the literature on the relation between IH and condomless sex may reflect a need for more nuanced studies, such as examining indirect effects or moderating variables (15, 16).…”
Section: Minority Stress: Ih In Relation To Risky Behaviorsmentioning
confidence: 99%
“…For example, lacking condom use self-efficacy can promote condomless anal sex by making BMSM feel doubtful about their abilities to use and discuss condoms with sexual partners [17]. Moreover, internalized homophobia, which is associated with decreased resilience levels [18], may promote condomless anal sex by diminishing BMSM’s perceived self-worth [19]. Internalized homophobia could also confound the association between resilience and condomless anal sex.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, despite the high prevalence of mental health concerns such as anxiety, depression, and substance abuse among PLWHA (Whetten, Reif, Whetten, & Murphy‐McMillan, ), few articles about the psychosocial implications of HIV/AIDS and effective treatments for PLWHA have been published in the flagship journal of the counseling field in recent years. The Journal of Counseling & Development has published only six articles since 2000 that explore HIV/AIDS within the United States (Amola & Grimmett, ; Buki, Kogan, Keen, & Uman, ; Hovell et al, ; Hunt, Jaques, Niles, & Wierzalis, ; Springer & Lease, ; Zeligman, Barden, & Hagedorn, ), two of which were published within the last decade. This amounts to an article every 2 to 3 years concerning an illness that has received tremendous attention in the fields of medicine, psychology, psychiatry, and social work.…”
Section: Hiv/aids As a Social Justice Issuementioning
confidence: 99%
“…In addition, research focusing on both HIV prevention approaches and effective therapeutic interventions can broaden and deepen clinical practice so that it aligns with current knowledge of HIV/AIDS. Some work has begun in this area, such as empirical explorations into social support, stigma, and posttraumatic growth among PLWHA (Zeligman et al, ) and HIV risk behaviors and internalized homophobia among young Black MSM (Amola & Grimmett, ). Studies such as these align with the advocacy standards in the ACA Code of Ethics by both illuminating and addressing “potential barriers and obstacles that inhibit access and/or the growth and development of clients” (ACA, , Standard A.7.a., p. 5).…”
Section: Hiv/aids As a Social Justice Issuementioning
confidence: 99%